AUDIT DAN TRANSPARANSI PENGELOLAAN KEUANGAN DAERAH KABUPATEN KUTAI BARAT - Imam Nazarudin Latif, Yovenalis Aâ€™ai. Elfreda Aplonia Lau. (EKONOMIA, 2015)
The financial statements are drawn up Upon Kutai Barat Regency is a structured report regarding the financial position and the transactions carried out by an entity reporting. Financial reporting is useful to present useful information for decision making and to show accountability and reporting entities.The formulation of the issue as to whether the financial statements are presented already meets Government accounting standards (SAP). Whether the financial statements are presented by a local government in Kutai Barat in Recommend Reasonable Without Exception (WTP).The theoretical foundations of financial accounting focus on financial statements presented meets Government accounting standards (SAP). Financial report on local government by the Kutai Barat serve in Recommend Reasonable Without Exception (WTP).As for the Hypothesis presented the financial report presented do not meet Government accounting standards (SAP). Financial reporting by local government serve in Â Kutai Barat in Recommend Reasonable with the exception of (WDP). that measurement, presentation and reporting in the Government of Kutai Barat Regency, has presented reasonably.The research results showed that the financial statements adequately disclosed, there was no disobedience influential direct and material. Measurement, presentation and reporting as well as control served yet reasonable and do not meet Government accounting standards (SAP). Thus this research hypothesis is accepted.